How Qualified is The Company’s Earning Quality: a Study of The 100 Most Liquid Indonesian Companies - Widjaja, Stefanie Evetania; Diana, Patricia (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2024)
Investor behavior can be reflected in the market price. Market price movement have strong correlation with market perspective about company earnings. Market does not always positively react to high earnings information, but should be high quality of earnings. High quality earnings can reflect the company's actual financial condition, which useful for investment decision making for investors, and determine business strategies for companies. The aim of this study is to obtain empirical evidence regarding the effect of earnings persistence, liquidity, growth opportunity, profitability, and capital structure toward earnings quality. The objects in this study are companies included in the Kompas100 Index, index that ranks 100 companies with the highest liquidity, consecutively during 2018-2020. Secondary data used was obtaining from financial reports and analyzed using multiple linear regression equations. This research found that companies which can generate profit from their main operation, not from foreign exchange or other income supposed to be companies with high quality earnings. Moreover, business strategic that such as market expansion, differentiation even though in the early stage judge can improve quality of earnings.